Ślad i (nie)obecność w twórczości Evy Kmentowej - Kempińska, Luiza (Artium Quaestiones, 2018)
Trace and Absence/Presence in the Art of Eva Kmentova Summary The topic of the paper is the sculpture of Eva Kmentova (1928-1980) from the late 1960s and early 1970s. Casts and impressions of the body, which make a significant part of the artist’s output, have been considered by critics and scholars as directly related to herself, and that allegedly close relationship has been taken for granted. The author proposes a different approach to Kmentova’s works. The related concept of presence has been based on Gianni Vattimo’s idea of the “week thought” and Jacques Derrida’s deconstruction. In such a perspective, the traces implied by Kmentova’s body impressions refer not so much to the subject’s presence, but rather to its absence. This claim has been developed in the interpretations of some of the artist’s works, such as Human Egg (1968), Footprints (1969), Feet (1970), and Figure on the Grass or Myself (1971), in which the status of the trace and its tenuous relation to the categories of presence and absence of the artist in her own oeuvre have been examined.